The relationship between small pelagic fish catches with sea surface temperature and chlorophyll in Makassar Strait waters - Rini Sahni Putri; Hasrianti Hasrianti; Damis Damis; Muhammad Bibin; Andi Rani Sahni Putri; Muh Kasim; Suhartono Nurdin (Jurnal Iktiologi Indonesia, 2022)
Makassar Strait is a waters area with a large and relatively fertile water resource potential. The Makassar Strait area represents the confluence zone between the Pacific Ocean and Indian Ocean fish populations. The fertility of the waters makes this area one of the breeding zones for most aquatic biota. This study aims to map the catch of small pelagic fishes with water conditions in the Makassar Strait. The data used in this study was fish catches data from Makassar Strait waters from June to September 2021. Data on environmental conditions in the form of Sea Surface Temperature and chlorophyll-a concentration in the waters during the study period were obtained from the AQUA satellite with MODIS sensors, then combined with the Geographic Information System (GIS). The results of this study indicate that the sea surface temperature range in Makassar Strait waters was between 26.7°C–31.3°C and the concentration of chlorophyll-a was between 0.7 mg/m³ - 1.30 mg/m³. The highest catch points were at two points with the same catch of the purse seine, namely 4,000 kg at 118°51'E and 5°10'59"S and at 118°52'59"E and 5°3'S, while the lowest catch was 5 kg at 118°19'E and 4°57'S. It can be concluded that the presence of fish may be influenced by the water’s conditions favored by the target fish in the Makassar Strait. Abstrak Selat Makassar merupakan kawasan perairan yang memiliki potensi sumberdaya perairan yang cukup besar dan relatif subur. Kawasan Selat Makassar merepresentasikan zona pertemuan antara populasi ikan Samudera Pasifik dan Samudera Hindia. Kesuburan perairannya menjadikan daerah ini sebagai salah satu zona berkembang biak bagi sebagian besar biota perairan. Penelitian ini bertujuan untuk memetakan hasil tangkapan ikan pelagis kecil dengan kondisi perairan di Selat Makassar. Data yang digunakan dalam penelitian ini merupakan data tangkapan ikan dari Perairan Selat Makassar pada bulan Juni-September 2021. Data kondisi lingkungan perairan berupa Suhu Permukaan Laut dan konsentrasi klorofil-a perairan pada periode penelitian diperoleh dari satelit AQUA dengan sensor MODIS, kemudian dikombinasikan dengan Sistem Informasi Geografis. Hasil penelitian ini menunjukkan bahwa kisaran suhu permukaan laut di Perairan Selat Makassar antara 26,7°C–31,3°C dan konsentrasi klorofil-a antara 0,7 mg/m³ - 1,30 mg/m³. Titik tangkapan tertinggi terdapat pada dua titik dengan hasil tangkapan pukat cincin yang sama yaitu 4000 kg pada 118°51’BT dan 5°10’59”LS serta pada titik 118°52’59”BT dan 5°3’LS, sedangkan tangkapan terendah sebanyak 5 kg pada titik 118°19’BT dan 4°57’LS. Disimpulkan bahwa keberadaan ikan kemungkinan dipengaruhi oleh kondisi perairan yang disukai ikan target tangkapan di Selat Makassar.